Assessment of collection samples of beans by economical-valued characteristics in the conditions of the Almaty region - Zhumabayeva, B.A.; Aitasheva, Z.G.; Lebedeva, L.P.; Alibekova, D.A.; Chunetova, Zh.Zh.; Shyngiskyzy, N. (Fundamental and Experimental Biology, 2021)
Comprehensive description of the collection material of vegetable common bean (Phaseolus vulgaris L.) by its origin and economically valuable characters is presented for the suitability of harvesting for the production line in conditions of the Almaty region. The vegetation period of selected bean varieties are studied, which enable the annual production of conditioned seeds of the field. Early ripe and mid-season forms of vegetable beans studied suitable for cultivation in the Almaty region are identified. It has been shown that the duration of the growing season of the material of vegetable beans under investigation has varied within 71–85 days. The most productive bean varieties for the conditions of the Almaty region have been indicated. Correlation ties between the yield and the components of productivity for the mass of green vegetable pods have been established. According to the structuralanalysis of the collection by productivity in the studied zone, the most promising and adapted varieties and lines in the early-ripe cluster are Laura and Luna varieties, which yield has exceeded the productivity of the reference variety by 22–37 %. At the same time, the mid-season cluster has revealed the Casablanca (Poland) variety, which has revealed 26 % higher productivity comparing to the yield of the same reference standard. The resistance of the selected vegetable bean representatives of the col-lection to anthracnose has been studied by using molecular genetically marking of genotypes.